(untitled) (Research, Society and Development, 2020)
Agroecological Street Markets (ASM) are places where organic products are grown in a sustainable system. The objective of this study was to identify the Sustainable Practices (SP) that are adopted by merchants and consumers participating in AF that occur in the city of Belém, PA. This research has a bibliographic and exploratory field character, being carried out from March to July 2020 in 5 ASM, being these: ASM of the brazilian agricultural research corporation of the state of Pará, Batista Campos square, Brasil square, brazilian service support for micro and Small enterprises and federal university of Pará. The methodology consisted of technical visits made in these places, where was stayed for about an hour, observing, making photographic records and using a table designed to identify SP adopted by sellers, buyers and aspects of the fair in general. The SP found at the fairs in Belém, were: By the merchants, the use of paper bags, the reuse of disposable bottles for the packaging of liquid products, the reuse of boxes for transporting products; by buyers, the use of a returnable bag, that was made incorrectly. Sustainable alternatives such as the use of returnable packaging and paper could be adopted by marketers and buyers at the street markets, as well as the presence of sellers of reusable products that bring alternatives to the consumer, reinforcing a sustainable proposal.